Strengthening Legal Protection for Women Victims of Domestic Violence: A Human Rights Perspective - Ami Nurafni (Edujavare Publishing, 2025)
Domestic violence against women constitutes a serious violation of human rights that requires comprehensive legal protection and effective state intervention. This study aims to analyze the strengthening of legal protection for women victims of domestic violence from a human rights perspective. The research employs a normative legal method using statutory, conceptual, and case approaches, with data derived from secondary legal materials such as legislation, international conventions, and academic literature. The findings reveal that although legal frameworks—both at international and national levels—have increasingly recognized domestic violence as a public issue and a human rights concern, significant challenges remain in their implementation. These challenges include limited access to justice, weak law enforcement, inadequate institutional support, and persistent socio-cultural barriers rooted in patriarchal norms. The study emphasizes that effective legal protection must go beyond formal regulation and adopt a victim-centered and holistic approach, integrating legal, social, and institutional mechanisms. It concludes that strengthening legal protection requires not only normative alignment with human rights principles but also practical efforts to ensure accessibility, enforcement, and prevention.